preliminary observation of teacher challenges in implementing home-based teaching and learning - Tasaratha Rajan Anamalai; Maizatul Hayati Mohamad Yatim (Pejabat Karang Mengarang UPSI, 2021)
In the wake of the COVID-19 epidemic, education systems struggle to function and achieve their intended goals. Globally, all children are affected, though to varying degrees, based on various factors, including the country/region where they live, their age, family background, and whether they had access to certain substitute/alternative educational opportunities throughout the pandemic. Most educational institutes have shifted to online learning platforms to keep academic activities going. However, the questions about the preparedness, designing and effectiveness of e-learning are still not clearly understood, particularly for a developing country like Malaysia, where the technical constraints like suitability of devices and bandwidth availability pose a severe challenge. The teaching profession in our country is the critical pillar in shaping the future of exceptional human beings. Thus, teachers and facilitators are responsible for ensuring the transmission of transparent and high-quality knowledge to students of all levels. The Covid-19 worldwide visible crisis that has struck the world today has had a variety of effects on a country's economy, society, and politics, as well as the field of education. Although there are other challenges, it focuses on the experience of instructors in adopting Home-Based Learning (HBL) with literature sources and prior studies.